Rotational Stability, Tilt and Decentration of a New IOL with a 7.0 mm Optic. (2nd November 2021) - Wendelstein, Jascha; Laubichler, Peter; Fischinger, Isaak; Mariacher, Siegfried; Beka, Sophie; Mursch-Edlmayr, Anna; Siska, René; Langenbucher, Achim; Bolz, Matthias
ABSTRACT: Purpose : To evaluate rotational stability, tilt and decentration of a new monofocal IOL with a 7.0 mm optic and frame haptics. Methods: Prospective post-market clinical follow-up study at the Kepler University Hospital Linz, Austria. An Aspira-aXA (HumanOptics, Germany) was implanted in 74 eyes of 42 cataract patients. The lens was manufactured with toric markings. IOL rotational stability was evaluated by comparing its position at the end of surgery (EoS) versus 1 day, 1 week, 1 month and 4 months postoperatively. IOL tilt and decentration were measured using a Scheimpflug camera at 1 week, 1 month and 4 months. Results: Median absolute IOL rotation was 1.42 degrees (n = 52; mean = 2.18 ± 2.23°) within 1 day after surgery and was significantly higher compared to all later intervals (median <1.0 degree; P = .001). At the 4 months follow-up, IOL rotation was within 5.0 degrees in 85% of the eyes (n = 40) and within 10.0 degrees in 98% (n = 46) of the eyes. The only eye with an IOL rotation of ≥ 10.ty0 degrees (EoS vs . 1 day) had an AL of 26.45 mm. At the last follow-up, the IOL vertical and horizontal tilt referenced to the pupillary axis was in average less than 1.5 degrees in both eyes (n = 54; maximum 5.85°). Decentration in both meridians was on average less than 0.10 mm in both eyes (maximum 0.30 mm). Conclusion: The one-piece Aspira-aXA IOL showed good and stable positioning within the capsular bag over a 4 months period.